The Fuzzy Control for Rotor Flux Orientation of the double-fed asynchronous generator Drive (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
In This paper we present a new contribution of fuzzy logic for electrical machine control. We are interested to the control direction of the rotor flux applied to Doubly-Fed Induction Generators (DFIG)At first, the principle of operation and modeling are applied to the DFIG is developed and introduced. Thereafter, the Fuzzy approach is applied to the FOC control, to improve the performance of the machines.Finally, the simulation results of the two commands are validates on the environment Matlab / Simulink followed by a detailed analysis.